Gas induced conversion of hybrid perovskite single crystal to single crystal for great enhancement of their photoelectric properties. Issue 41 (12th October 2017) - Ju, Dianxing; Zhao, Tianyu; Yangyang, Dang; Zhang, Guodong; Hu, Xiaobo; Cui, Deliang; Tao, Xutang
Abstract : Gas induced conversion of hybrid perovskite single crystal to single crystal for great enhancement of photoelectric properties with their morphology retained. Abstract : The desired morphology, narrowed band gap and good photoelectric properties are the key factors for achieving the wide application of hybrid perovskite materials. During the preparation of novel hybrid perovskite materials, preserving the morphology of highly crystalline materials and narrowing their band gap will be desirable for designing photoelectric devices with outstanding performance. Here, with broad band gap 1D/2D hybrid perovskite single crystals as a template, we design a universal conversion process from single crystal to single crystal for a variety of large-sized hybrid perovskite materials induced by CH3 NH2 (MA) gas under an ambient atmosphere. Most significantly, the hybrid perovskite single crystals keep their original morphology, narrow their optical band gap, and enhance their carrier mobility and photo-response dramatically after induced conversion by MA gas molecules, especially for DMAPbI3 (NH2 (CH3 )2 PbI3 ). The optical band gap of DMAPbI3 was lowered from 2.58 eV to 1.53 eV and its photo-response performance was enhanced greatly by even a small amount of replacement of DMA + by MA +, which provides a new idea for designing novel hybrid perovskite single crystals with a desired morphology and their optoelectronic devices with good performance.